Laterality of lower limbs and relationship with the plantar pressure distribution in the static balance - *Carmen Mayolas Pi*, Adoración Villarroya Aparicio*, Joaquín Reverter Masia** (FEADEF, 2011)
The distribution of loads during gait has been evaluated in many studies, some of which have been seen to influence the handedness of the individual in this distribution. However, in the static pool, several studies have been carried out which assess the possible causes of inequitable distribution of the charges, some according to the vision or adjoining space and according to influence of visual laterality. In our study we will observe the influence of the lateral lower limb preference in the distribution of the load on the sole of the foot, using three tests to assess the lateral dominance: shoot with precision, dynamic balance and static balance (Maupas et al. 2002). According to our results, lower limb lateral preference does not influence significantly the distribution of charges in the sole of the foot, however, we observe a tendency to increase the load/weight on the left limb in righthanded people (according to tests of balance dynamic and precision shot) and on the right limb in left handed people